1996
DOI: 10.1104/pp.110.2.425
|View full text |Cite
|
Sign up to set email alerts
|

Plant Cell Growth Responds to External Forces and the Response Requires Intact Microtubules

Abstract: Microfibril deposition i n most plant cells i s influenced by cortical microtubules. Thus, cortical microtubules are templates that provide spatial information to the cell wall. How cortical microtubules acquire their spatial information and are positioned is unknown. There are indications that plant cells respond to mechanical stresses by using microtubules as sensing elements. Regenerating protoplasts from tobacco (Nicotiana tabacum) were used to determine whether cells can be induced t o expand in a prefere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
71
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(76 citation statements)
references
References 15 publications
4
71
0
1
Order By: Relevance
“…Immunocytochemical staining of microtubules showed that control protoplasts displayed randomly oriented cortical microtubules as already described [30] (Fig. 2A).…”
Section: Resultsmentioning
confidence: 82%
“…Immunocytochemical staining of microtubules showed that control protoplasts displayed randomly oriented cortical microtubules as already described [30] (Fig. 2A).…”
Section: Resultsmentioning
confidence: 82%
“…The orientation of cortical microtubules is under the control of environmental signals, such as gravity. For example, hypergravity promoted reorientation of microtubules into parallel arrays in protoplasts from Nicotiana tabacum (Wymer et al, 1996) and Brassica napus (Skagen and Iversen, 1999). Also, hypergravity induced reorientation of cortical microtubules from transverse to longitudinal directions in azuki bean epicotyls (Soga et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other eukaryote cells, vacuolated and cell wall-confined plant cells follow a specialized mode of cytokinesis, exhibiting four major microtubular arrays at different cell cycle stages with a variety of functions (Goddard et al, 1994). During interphase, a cortical array consisting of parallel microtubules oriented perpendicular to the cell expansion axis assists cellulose deposition (Cyr, 1994) and responds to stimuli (Wymer et al, 1996). At the onset of mitosis, the cortical array is replaced by a densely packed ring of microtubules encircling the nucleus called the preprophase band (PPB), which defines the location of the cell plate formed during cytokinesis (Mineyuki, 1999).…”
Section: Introductionmentioning
confidence: 99%